Sustainable Development Evaluation and Its Obstacle Factors of the Weihe River Basin in Shaanxi Province, China - Wang, Yirui; Song, Jinxi; Zhang, Xuexian; Sun, Haotian (Frontiers in Earth Science, 2021)
The contradiction between economic growth, social development and water environment deterioration represent significant challenges for river basin sustainable development. By constructing an indicator system of river basin sustainable development, the entropy method is adopted to conduct a quantitative evaluation of the cities sustainable development level for the Weihe River Basin in Shaanxi Province from 2009 to 2018, and the standard deviational ellipse is used to analyze the evolution of spatial distribution pattern of sustainable development in the study area. Furthermore, the obstacle degree model is applied to analyze the main obstacle factors restricting the improvement of river basin sustainable development. The results show that the sustainable development level of the Weihe River Basin in Shaanxi Province improved slowly during the study period, and significant regional differences among cities. This study provides a novel approach for future evaluation on sustainable development of the Weihe River Basin and even the arid region in Northwest China, to achieve a win-win situation between economic and social development, and ecological environment protection.